Role of ABC and Solute Carrier Transporters in the Placental Transport of Lamivudine - Ceckova, Martina; Reznicek, Josef; Ptackova, Zuzana; Cerveny, Lukas; Müller, Fabian; Kacerovsky, Marian; Fromm, Martin F; Glazier, Jocelyn D; Staud, Frantisek (Antimicrobial agents and chemotherapy, 2016)
Lamivudine is one of the antiretroviral drugs of choice for the prevention of mother-to-child transmission (MTCT) in HIV-positive women. In this study, we investigated the relevance of drug efflux transporters P-glycoprotein (P-gp) (MDR1 [ABCB1]), BCRP (ABCG2), MRP2 (ABCC2), and MATE1 (SLC47A1) for the transmembrane transport and transplacental transfer of lamivudine. We employed in vitro accumulation and transport experiments on MDCK cells overexpressing drug efflux transporters, in situ-perfused rat term placenta, and vesicular uptake in microvillous plasma membrane (MVM) vesicles isolated from human term placenta. MATE1 significantly accelerated lamivudine transport in MATE1-expressing MDCK cells, whereas no transporter-driven efflux of lamivudine was observed in MDCK-MDR1, MDCK-MRP2, and MDCK-BCRP monolayers. MATE1-mediated efflux of lamivudine appeared to be a low-affinity process (apparent Km of 4.21 mM and Vmax of 5.18 nmol/mg protein/min in MDCK-MATE1 cells). Consistent with in vitro transport studies, the transplacental clearance of lamivudine was not affected by P-gp, BCRP, or MRP2. However, lamivudine transfer across dually perfused rat placenta and the uptake of lamivudine into human placental MVM vesicles revealed pH dependency, indicating possible involvement of MATE1 in the fetal-to-maternal efflux of the drug. To conclude, placental transport of lamivudine does not seem to be affected by P-gp, MRP2, or BCRP, but a pH-dependent mechanism mediates transport of lamivudine in the fetal-to-maternal direction. We suggest that MATE1 might be, at least partly, responsible for this transport.
Keywords: placenta; Cell Line; biologický transport; proteiny přenášející organické kationty; buňky MDCK; Pregnancy; ATP-Binding Cassette Transporters; proteiny spojené s mnohočetnou rezistencí k lékům; ATP Binding Cassette Transporter, Subfamily B; Placenta; Humans; zvířata; krysa rodu Rattus; P-glykoproteiny; potkani Wistar; Animals; Biological Transport; Female; psi; Lamivudine; ženské pohlaví; ABC transportéry; Dogs; Multidrug Resistance-Associated Proteins; buněčné linie; Organic Cation Transport Proteins; lamivudin; Rats; těhotenství; Madin Darby Canine Kidney Cells; lidé; Rats, Wistar